Are Biases Related to Attrition, Missing Data, and the Use of Intention to Treat Related to the Magnitude of Treatment Effects in Physical Therapy Trials?: A Meta-Epidemiological Study. (3rd June 2022) - Armijo-Olivo, Susan; R. da Costa, Bruno; Ha, Christine; Saltaji, Humam; Cummings, Greta G.; Fuentes, Jorge
Abstract: The objective of this study was to determine the association between biases related to attrition, missing data, and the use of intention to treat and changes in effect size estimates in physical therapy randomized trials. A meta-epidemiological study was conducted. A random sample of randomized controlled trials included in meta-analyses in the physical therapy discipline were identified. Data extraction including assessments of the use of intention to treat principle, attrition-related bias, and missing data was conducted independently by two reviewers. To determine the association between these methodological issues and effect sizes, a two-level analysis was conducted using a meta-meta-analytic approach. Three hundred ninety-three trials included in 43 meta-analyses, analyzing 44, 622 patients contributed to this study. Trials that did not use the intention-to-treat principle (effect size = −0.13, 95% confidence interval = −0.26 to 0.01) or that were assessed as having inappropriate control of incomplete outcome data tended to underestimate the treatment effect when compared with trials with adequate use of intention to treat and control of incomplete outcome data (effect size = −0.18, 95% confidence interval = −0.29 to −0.08). Researchers and clinicians should pay attention to these methodological issues because they could provide inaccurate effect estimates. Authors and editors should make sure that intention-to-treat and missing data are properly reported in trial reports.